EBI training for teachers by integrative projects and itinerant support - Guzmán Sota, Ingrid (2021)
This article was prepared by the Faculty of Education, through the Professional School of Education and the Intercultural Bilingual Education (IBE) department. Its purpose is to share some reflections based on the academic actions implemented during 2020 (a peculiar year characterized by the healthcare crisis caused by the Covid-19 pandemic). The article includes a brief diagnosis of the educational conditions of students, the framework of reference considered for the proposal, the hypotheses or assumptions that motivated the actions, the approach adopted and the implemented actions or methodological strategies applied in the educational process of students, as well as some key preliminary conclusions to understand the importance of higher education in intercultural bilingual education situated and paying attention to the processes of cultural change experienced by students as well as the demands of the territory with its cultural and linguistic characteristics.